THE ADVANTAGES AND DISADVANTAGES OF NANOTECHNOLOGY - Cristina-Maria Gavrilescu; Cringuța Paraschiv; Paloma Horjinec; Diana-Maria Sotropa; Roxana-Mihaela Barbu (Romanian Society of Oral Rehabilitation, 2018)
Nanomaterials are natural or manufactured objects that have at least one of their external dimensions in the nanoscale (in the range of 1-100 nm) and a specific surface area by volume greater than 60 m² cm ̄ ³. They are called nanoparticles when they have all three dimensions in the nanoscale. Intrinsic properties of engineered nanomaterials, designed for a specific purpose, provide unique functions to these nano-objects, whose manufacture and use are exponentially increasing. Nanotechnology offers an explosion of techniques, methods, and products that bring huge advantages for medicine, industry, information, communication or agriculture. Dentistry benefits of nanotechnology in disease prevention and diagnosis, in bone regeneration, restaurative dentistry, dental implants and tissue regeneration. As in every human domain, evidence begins to point to the fact that along with the positive changes brought by nanotechnologies, they may also cause toxic effects for human health and for the environment security. The mechanisms of nanotoxicity are not yet completely understood, but toxic effects produced by nanoparticles have been recognized for pulmonary, reproductive, cardiac, digestive, cutaneous and immune levels. Nanomaterials can also cause air, water and most important a soil persistent form of pollution, which is too small to be detected easily, making nanopollution another manmade unwanted environmental impact, with uncertain effects in the long term. Larger and multicenter studies are needed to determine the human reactivity and the fate of the nanoparticles in the environment before large-scale nanotechnology is completely settled.